Lietuvių kalbos zoomorfizmų semantinės struktūros sistemiškumas - Rosinienė, Gražina (Baltistica, 1989)
ON SYSTEMATIC CHARACTER OF THE SEMANTIC STRUCTURE OF LITHUANIAN ZOOMORPHISMSIn the paper an attempt has been made to establish three types of systematic relations, namely, hierarchical, associative and associative-hierarchical, in the semantic structure of Lithuanian zoomorphisms, or animal terms in figurative use.The above relations exist in the meanings of one and the same zoomorphism as well as among all the zoomorphisms in question. They can be determined by the components of the semantic structure under discussion, i. e. by the content plane and the forms of realization of the content plane in speech.
Keywords: lietuvių kalba; zoomorfizmai